Management Direction in the School Improvement of the Educational Institutions of the Metropolitan District of Quito: A Question of Aptitude and Attitude (Docentes 2.0 Journal, 2020)
This essay is focused on analyzing what competencies should the manager have for the management and improvement of an educational center ?, for which it has been necessary to obtain relevant theoretical information from the various authors in educational matters such as Fullan (2002), Bolívar (2018), Murillo-Torrecilla (2013), Díaz-Barriga (2006), among other researchers who have contributed significantly to learning, relearning the educational phenomenon. A good school manager must always be focused on both general and generic competencies that he must possess in educational matters. Both internal and external school management of the Ecuadorian director must take into account their training bases, experience in educational work guaranteed by the necessary skills for their management in front of teachers, parents, mainly to solve the learning needs of students, as well as efficiently respond to the demands of all instances of the national educational organization. The competent Ecuadorian manager, with an effective and efficient educational management base, must take into account the attitude manifested in all his actions, therefore, the means to achieve excellence in educational institutions must necessarily be carried out through the permanent exercise of a transformative, participatory leadership that guides, engages, stimulates and above all unites the efforts of all members of the educational community, to assume all institutional educational projects as their own, that the participation of each of them is as important as significant.
Keywords: Competences; school management; management process; leadership